Penggunaan Rumus Holliday Segar pada Pasien Pediatrik yang Dilakukan Anestesi - Sari, Djayanti; Widyastuti, Yunita; Gunawan, Fanny (Jurnal Komplikasi Anestesi, 2020)
Intravenous fluid theraphy in acute ill patient has been the subject of health practices for more than 50 years. The development of knowledge in dealing with patients and illness has raised questions about the validity of Holliday Segar formula. Many researchers found hyponatremia in pediatric patient who were hospitalized and received intravenous fluid theraphy using the Holliday Segar formula. This thread tries to review the use of the Holliday Segar formula based on research studies that have been conducted.